Symbols And Mob Mentality in Short Story “The Lottery” By. Shirley Jackson - Aji, Galang Rambu; Rahayu, Endang Yuliani (Universitas Negeri Makassar, 2024)
Abstract. This study aims to discuss the symbolic components in Shirley Jackson's